ผลของแคลเซียมซิลิเกตจากอุตสาหกรรมซีเมนต์ต่อการเจริญเติบโตและการตอบสนองกระบวนการทางสรีรวิทยาของข้าวเหนียวพันธุ์ กข-แม่โจ้ 2 ภายใต้สภาวะขาดน้ำ - หะยีลาเต๊ะ, ณิชนันทน์; ชคตระการ, สมชาย; ภูมิพันธ์, พักตร์เพ็ญ; ชุติมานุกูล, พฤกษ์ (Thai Journal of Science and Technology, 2020)
Water deficiency is the most important effect on growth and physiological responses of glutinous rice, which is affected to its quantity and quality. The aim of this study was to estimate an effect of calcium silicate from cement industry on growth and yield of glutinous rice cv. RD-Mae Jo 2 under different water supplies. The experiment was undertaken in 3×5 factorial in completely randomized design. The study factors were; (1) different water supplies, (100, 50 and 25 % of moisture at soil saturated with water), and (2) calcium silicate (0, 50, 150, 300 and 400 Kg/rai). The result showed that decreased water supply affected rice cv. RD-Mae Jo 2; growth (plant height, leaf width, leaf length and tiller number per plant), stomatal conductance and respiration rate were decreased, while the photosynthetic rate was increased. Decreased water supply to 50% with calcium silicate 400 Kg per rai promoted growth characteristics such as height, leaf length and tiller number per plant (significantly higher than those of non-calcium silicate). Moreover, photosynthetic rate was highest and trended to decrease respiration rate when compared to decreased water supply to 50% with non-calcium silicate. Therefore, calcium silicate from cement industry can be used to replace expensive silicon fertilizer and to alleviate stress caused by water deficiency of rice.